Short selling and inside information - Fazio, Dimas Mateus (2014)
Using data on all lending deals in the Brazilian stock market from 2009 to 2011, we provide answers to the following questions: i) are short-sellers informed in Brazil?, ii) which short sellers are informed?, and iii) how are they informed? The answer to the first question is positive, the average Brazilian short-seller is informed. Among these short-sellers, individual investors appear to be as informed as investment funds. To provide an answer to the third question, the approach is to observe how short-selling behaves around days when relevant corporate news is disclosed. This paper shows that funds are more informed just after the disclosure of news, an indication that these investors decide their short-selling operations after processing the news. On the other hand, individual investors increase short-selling prior to bad news and decrease short-selling prior to good news. This last result could be a sign of information leakages from insiders.